Intestinal occlusion due to mixed hemangioma in greater omentum - Mejía, Daniel Zúñiga; Hernández, Javier Andrés Meza; Trejo, Isabel Serrano; Astudillo, Christian Marcelo Carrión; Martínez, Angélica Samantha Silva (International Journal of Research in Medical Sciences, 2023)
Omental tumors are most commonly found in the pediatric population, with hemangiomas being one of the rarest types. These tumors can occur in any organ, with a higher prevalence in the skin and subcutaneous tissue. Although they are extremely rare, omental tumors, including hemangiomas, often involve the greater omentum. We present the case of a 70-year-old male patient that presented to our hospital with abdominal pain, distension, and inability to pass stool. After histopathological analysis we confirmed a mixed cavernous as well as capillary hemangioma of the omentum.